RESPONS AGRONOMIS EDAMAME VARIETAS RYOKO TERHADAP VARIASI JARAK TANAM DAN DOSIS PUPUK KALIUM NITRAT (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2026)
This study aims to determine the effect and interaction between planting distance and white potassium nitrate (KNO3) fertilizer dosage on the growth and yield of Ryoko variety edamame (Glycine max (L.) Merill) plants. The study was conducted in Tegal Parean Sukatani, Agricultural, Fisheries, and Forestry Extension Center, Ngamprah District, West Bandung Regency, West Java Province. The design used was a factorial randomized block design (RBD) with three replications. Factor I was planting distance: d1 = 20 cm × 15 cm, d2 = 30 cm × 25 cm, and d3 = 40 cm × 35 cm. Factor II was the dosage of white KNO3 fertilizer: k1 = control, k2 = 100 kg/ha, and k3 = 200 kg/ha. Observations were made on: plant height, number of leaves, number of branches, number of pods per plant, pod weight per plant, and pod weight per plot.The results showed an interaction between planting distance and white KNO3 dosage on the number of leaves at 42 days after planting, with the best combination found in treatment j2k1 (planting distance 30 cm × 25 cm and control dosage). An interaction also occurred in the parameter of pod weight per plot, with the best combination found in j1k2 (planting distance 20 cm × 15 cm and dosege 100 kg/ha). Meanwhile, in terms of independent effects, a planting distance of 20 cm × 15 cm (j1) had a significant effect on plant height, while a planting distance of 40 cm × 35 cm (j3) resulted in the highest number of pods per plant and pod weight per plant. The independent application of white KNO3 fertilizer showed that the control dose (k1) resulted in the best plant height growth.